THE COMPARISON OF PLAQUE INDEX BEFORE AND AFTER RINSING WITH FUJI APPLE (Malus sylvestris) EXTRACT0 100% AND CHLORHEXIDINE 0,2% IN CHILDREN AGED 8-10 YEARS - Ihsan, Muhammad Fauzan; Aspriyanto, Didit; Erlita, Isyana (Dentino : Jurnal Kedokteran Gigi, 2018)
Background:The mixed dentition occurs in children aged 8-10 years, the change from deciduous teeth to permanent teeth. The children at this age is susceptible to oral disease because they favor to consume cariogenic foods that can cause the buildup of plaque on the teeth. Plaque is a gray-ish yellow substance that is firmly attached to the tooth surface. Plaque can be controlled with chemical treatment such as using a mouthwash. Chlorhexidine 0,2% is the most potential antimicrobial mouthwash in reducing plaque but chlorhexidine 0,2% has side effects to the oral cavity so herbal ingredients begin to be an alternative choice. Fuji applet (Malus sylvestris) contains flavonoids and tannins that are antibacterial to inhibit plaque growth. Purpose: To know the comparison of plaque index before and after rinsing with Fuji apple(Malus slyvestris) extract 100% solution and chlorhexidine 0,2% in children aged 8-10 years old.Method: This study used quasi experimental with pre-posttest with control group design The total sample was 62 people, consisted of 2 groups. Results: In the study, there was a greater decrease in plaque index score in rinsing group with Fuji apple(Malus slyvestri) extract 100% than with chlorhexidine 0.2%. The plaque index score decreased in the treatment group by 4.7% and in the control group only 3.1%. Conclusions: There are differences in plaque index scores before and after rinsing with Fuji apple(Malus sylvestris) extract 100% with chlorhexidine 0,2% in children aged 8-10 years old.